Flood Forecasting System Development for the Upper Ping River Basin - Nutchanart Sriwongsitanon (Agriculture and Natural Resources, 2010)
A flood forecasting system for the upper Ping River basin located in Northern Thailand was developed as a flood mitigation measure. The system comprised the URBS model (a rainfall-runoff model) used for runoff estimation, the FLDWAV model (a hydrodynamic model) used for flood routing investigation, and a database system for data storage and data management to facilitate model application. URBS was used to simulate hydrographs at five runoff stations located along the main stream of the Ping River and at 10 stations on its tributaries. FLDWAV was used to route flood hydrographs along the Ping River between the most upstream station at P.20 and the most downstream station at P.73 (approximately 198 km in length). Flood hydrographs of ungauged catchments between P.20 and P.73 were estimated using URBS, then were input into FLDWAV. The flood forecasting system proved effective in accurately simulating flood hydrographs along the Ping River and its tributaries and can be applied for flood mitigation purposes in flood risk areas, such as the cities of Chiang Mai and Lamphun.